TRADISI KATOBA SEBAGAI WARISAN BUDAYA DALAM MENGUATKAN PENDIDIKAN ISLAM PADA ANAK DI KABUPATEN MUNA SULAWESI TENGGARA - Faldin Baen; Muhamamd Ilham (Jurnal Pendidikan Sultan Agung, 2025)
AbstractThis study aims to examine the role of the Katoba tradition in shaping Islamic character in the children of the Muna tribe in Muna Regency, Southeast Sulawesi. Katoba is a traditional ritual that is passed down from generation to generation and is an integral part of the life cycle of the Muna people. This tradition integrates local values with Islamic teachings, and is carried out before the child enters puberty as a form of moral and spiritual education. This research uses a qualitative method with a library research approach, relying on various literary sources such as books, articles, and scientific journals to explore the meaning and values contained in the Katoba procession. The results of the study show that Katoba teaches the values of monotheism, birrul walidain (filial piety to parents), as well as honesty and responsibility in protecting the rights of others. This tradition plays an important role in shaping children's personalities, guiding them to understand their relationship with God, parents, and society, and strengthening the internalization of Islamic values from an early age. Thus, Katoba is not only a means of preserving local culture but also an effective medium for Islamic character education.